GAMBARAN STATUS KECACATAN KUSTA PADA PENDERITA KUSTA DI KABUPATEN BLORA - Umaya Umaya; Mateus Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Leprosy is a communicable disease that can cause permanent physical deformities. According to data from Health Department of Blora District, it was known that Public Health Center of Kunduran and Bogorejo had the highest new cases, with an increasing trend during the last 3 years. Those two PHCs still had 'high' grade 2 disability compared with national target. This research aimed to describe some factors related to the occurrence of disability in leprosy. This research is a descriptive observational with cross sectional design. Population of this research are 83 people affected by leprosy, registered in two PHCs during the last 3 years. These results indicated that the proportion of disability is higher in lepers with non productive age (38,5%), male (32,0%), having low education (36,8%), having good knowledge (55,6%), having no job (55,6%), multibacillary leprosy (36,5%), experiencing lepra reaction (50,0%), having delay of treatment >1 year (44,4%), having nerve impairment (100,0%), doing wound care (100,0%), and without support of family members (33,3%). This research concluded that the proportion of disability found higher in lepers with non productive age, male, having low education, having good knowledge, having no job, having multibacillary leprosy, experiencing lepra reaction, having delay of treatment >1 year, having nerve impairment, doing wound care, and without support of family members. This research suggest to the PHCs to give more counseling and training to the lepers about wound care and provide them tools to do this. Family members are expected to oversee the lepers when consuming MDT and reminds them to complete the treatment.